Agricultural socialized services and grain yield per unit area: empirical evidence from Jiangxi Province, China - Liao, Lichen; Guo, Jinyong; Peng, Yuanyuan; Liu, Yanduo; Ling, Yinqi; Tang, Yonghong (Frontiers in Sustainable Food Systems, 2025)
ObjectiveGiven limited cultivated land resources, increasing grain yield per unit area is crucial to ensure food security. Although China’s total grain production has increased for 20 consecutive years and remained above 6.5 × 108 t for nine consecutive years, the contribution rate per unit yield still needs to be improved. Agricultural socialized service is essential in promoting sustainable food production in China, which can drive land cultivation and grain increase.MethodsUsing survey data from 893 rice farmers in Jiangxi Province, China. This paper adopted the OLS model and intermediary effect model to explore the impact of agricultural socialized service on grain yield per unit area and its mechanism and further analyzed the heterogeneity of agricultural socialized service adoption on grain yield per unit area under different regions, farmland, and farm household types.Results(1) Agricultural socialized service had a significant positive effect on grain yield per unit area, which passed the endogeneity and robustness tests. (2) The adoption of agricultural socialized services by farmers will enhance the machinery use of the rice production process, promote the large-scale development of agricultural operations, and drive the “grain-oriented” planting structure, thereby achieving an increase in grain yield per unit area. (3) The heterogeneity test showed that agricultural socialized service had a more significant effect on promoting grain yield per unit area of farmers in grain-producing counties, farmers with low land fragmentation degree, farmers with a high degree of part-time employment and farmers with strong digital ability.ConclusionThis study emphasizes the potential of agricultural socialized services for grain yield per unit area and plays a crucial role in ensuring food security. By attaching importance to the supply–demand side benefits of agricultural social services, improving the availability of agricultural social services, and guiding farmers to cultivate grain scientifically, policymakers can use these insights to formulate targeted measures and fully exploit their optimal benefits.